Analisis Dampak Hukum Perlindungan Konsumen Dalam Perdagangan Online (Menelaah Dampak Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Online) - siagian, yeremi; Siregar, Mirna Salifah; Ananda, Bunga; Purba, Bonaraja (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The ability to trade within the country has made technological advancements in online trading exponentially more popular in recent years. The purpose of this article is to determine whether the country's current consumer protection laws are still applicable in light of the growing trend of digitalization of the economy and what steps should be taken to address legal issues that may arise. This article is written using normative juridical techniques, namely the approach of legal sources and law as a means of literary study. Legal issues arising during the current digital economy cannot be accommodated by Law Number 8 Year 1999 on Consumer Protection. Consumer protection is one of the most important topics in the online world commerce. Within many cases, consumers are less powerful than vendors and service providers, especially in terms of information availability, product dependability and safe transactions. Nonetheless, Indonesian laws offer legal guarantees to customers in e-commerce transactions. The surge in internet connectivity among Indonesians has coincided with tremendous growth in e-commerce in the country.